A Genome Wide Study of Copy Number Variation Associated with Nasopharyngeal Carcinoma in Malaysian Chinese Identifies CNVs at 11q14.3 and 6p21.3 as Candidate Loci - Low, Joyce Siew Yong; Chin, Yoon Ming; Mushiroda, Taisei; Kubo, Michiaki; Govindasamy, Gopala Krishnan; Pua, Kin Choo; Yap, Yoke Yeow; Yap, Lee Fah; Subramaniam, Selva Kumar; Ong, Cheng Ai; Tan, Tee Yong; Khoo, Alan Soo Beng; et al. (PloS one, 2016)
Nasopharyngeal carcinoma (NPC) is a neoplasm of the epithelial lining of the nasopharynx. Despite various reports linking genomic variants to NPC predisposition, very few reports were done on copy number variations (CNV). CNV is an inherent structural variation that has been found to be involved in cancer predisposition. A discovery cohort of Malaysian Chinese descent (NPC patients, n = 140; Healthy controls, n = 256) were genotyped using Illumina® HumanOmniExpress BeadChip. PennCNV and cnvPartition calling algorithms were applied for CNV calling. Taqman CNV assays and digital PCR were used to validate CNV calls and replicate candidate copy number variant region (CNVR) associations in a follow-up Malaysian Chinese (NPC cases, n = 465; and Healthy controls, n = 677) and Malay cohort (NPC cases, n = 114; Healthy controls, n = 124). Six putative CNVRs overlapping GRM5, MICA/HCP5/HCG26, LILRB3/LILRA6, DPY19L2, RNase3/RNase2 and GOLPH3 genes were jointly identified by PennCNV and cnvPartition. CNVs overlapping GRM5 and MICA/HCP5/HCG26 were subjected to further validation by Taqman CNV assays and digital PCR. Combined analysis in Malaysian Chinese cohort revealed a strong association at CNVR on chromosome 11q14.3 (Pcombined = 1.54x10-5; odds ratio (OR) = 7.27; 95% CI = 2.96-17.88) overlapping GRM5 and a suggestive association at CNVR on chromosome 6p21.3 (Pcombined = 1.29x10-3; OR = 4.21; 95% CI = 1.75-10.11) overlapping MICA/HCP5/HCG26 genes. Our results demonstrated the association of CNVs towards NPC susceptibility, implicating a possible role of CNVs in NPC development.